Construindo o discurso escrito: histórias e cartas “entre a oralidade e a escrita” (Revista de Estudos da Linguagem, 2000)
This article is a reworking of two moments of a research project entitled “Between orality and writing”, a study of the genesis of written discourse in children who are learning how to write: the firstmoment is concerned with narrative, the second with letter writing.In both these moments, language is seen as a system organized in and for social interaction, composed of the grammatical,semantic and discursive sub-systems, and human cognition is interpreted as a socially mediated process of subjective construction. We analyze the enunciative activity of children, obtaining evidence of their linguistic skill and their progress in the construction of the discursive styles being studied.